Specialised protagonists in a plant–pollinator interaction: the pollination of Blumenbachia insignis (Loasaceae). (10th December 2019) - Siriani‐Oliveira, S.; Cerceau, I.; Schlindwein, C.
Abstract: Analyses of resource presentation, floral morphology and pollinator behaviour are essential for understanding specialised plant‐pollinator systems. We investigated whether foraging by individual bee pollinators fits the floral morphology and functioning of Blumenbachia insignis, whose flowers are characterised by a nectar scale‐staminode complex and pollen release by thigmonastic stamen movements. We described pollen and nectar presentation, analysed the breeding system and the foraging strategy of bee pollinators. We determined the nectar production pattern and documented variations in the longevity of floral phases and stigmatic pollen loads of pollinator‐visited and unvisited flowers. Bicolletes indigoticus (Colletidae) was the sole pollinator with females revisiting flowers in staminate and pistillate phases at short intervals, guaranteeing cross‐pollen flow. Nectar stored in the nectar scale‐staminode complex had a high sugar concentration and was produced continuously in minute amounts (~0.09 μl·h −1 ). Pushing the scales outward, bees took up nectar, triggering stamen movements and accelerating pollen presentation. Experimental simulation of this nectar uptake increased the number of moved stamens per hour by a factor of four. Flowers visited by pollinators received six‐fold more pollen on the stigma than unvisited flowers, had shortened staminate and pistillate phases and increased fruit and seed set. Flower handling and foraging by Bicolletes indigoticus were consonant with the complex flower morphology and functioning of Blumenbachia insignis . Continuous nectar production in minute quantities but at high sugar concentration influences the pollen foraging of the bees. Partitioning of resources lead to absolute flower fidelity and stereotyped foraging behaviour by the sole effective oligolectic bee pollinator. Abstract : Flowers of Blumenbachia insignis have a unique flower morphology typical for Loasaceae, which is characterized by a complex androecium. Gradual pollen presentation by stamen movements and continuous nectar production in the five nectar scales shape the foraging behaviour of the oligolectic colletid bee pollinator.